Synthesis and Structural Studies on Some Coordination Complexes of Organotin (IV) with Macrocyclic Crown Ethers. - P.R. SHUKLA, MRS.; SATTAR, ASMA (Asian Journal of Chemistry, 2010)
Three series of hexa-coordinated complexes of organotin (IV) with three different crown ethers have been synthesized having the general formula Ph2Sn(L1-3)X2 where X = CI-, NO3-, CIO4- and SCN- and L1, L2 and L3 are the crown ether ligands (18—C—6) = 1, 4, 7, 10, 13, 16-hexaoxacycloocta- decane; (15-C-5) = 1,4,7, 10,13-penta-oxacyclopentadecane and (12-C-4)-1,4, 7 ,10-tetraoxacyclododecane. These complexes were characterized by elemental analysis, molar conductance data, IR and 1H NMR spectra and these results show that only four oxygen atoms of ligands and two phenyl groups are coordinated to tin giving an octahedral structure.